Dietary protein intake and health-related outcomes: a methodological protocol for the evidence evaluation and the outline of an evidence to decision framework underlying the evidence-based guideline of the German Nutrition Society - Kroke, Anja; Schmidt, Annemarie; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Haardt, Julia; Bauer, Jürgen M.; Bischoff-Ferrari, Heike; Böing, Heiner; Egert, Sarah; Ellinger, Sabine; Kühn, Tilman; et al. (European journal of nutrition, 2022)
Evidence-based guideline, Protein intake, Method, Prevention, Nutrition-related diseases